Proses Pembuatan Ready to Wear Fantasi Perpaduan Kain Batik Melalui Kajian Estetika pada Budaya Jepang - Rista Meyliana; Mien Zyahratil Umami (Garina, 2024)
Ready To Wear Fantasy Knight Princess The combination of Batik through Aesthetic Studies in Japanese Culture was taken because it was inspired by anime, manga and other stories in Japanese culture with a storyline of a tough princess. That is why the author interested in making a dress that suits the heroine. Even though, it has a simple design and beautiful batik motif but the clothes worn were suitable with the chivalrous spirit. Uniting Indonesian culture with Japanese culture by having aesthetic value on batik motifs. Making Ready To Wear Fantasy Princess Knight has the aim of knowing the suitable of batik motifs into fantasy clothing. This study used a qualitative method which described descriptively. Making Ready To Wear fantasy has the same steps of making clothing as other clothing manufactures. The process of making clothing includes, 1) determining the design, 2) preparing tools and materials, 3) applying measurements, 4) making basic patterns, 5) cutting materials, 6) painting fabrics, 7) merging materials, 8) ironing upholstery, 9 ) sewing clothes, and finishing to become the desired clothing. The process of making tasel ropes in ready to wear fantasy needs to be stretched one by one so that it gets neat results. Besides, when making cloth painting in the ironing process it must be at normal temperature and covered with fabric.